Taâ€™á¹¡Ä«r al-BÄ«ah al-Lughawiyyah â€˜alÄ Taâ€™lÄ«m al-Lughah al-â€˜Arabiyyah: DirÄsah al-MuqÄranah Baina al-Maâ€™had Baitul Arqam Jember wa al-Maâ€™had al-Kauá¹¡ar Sidorejo - Mahmudi, Hafid (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
The focus of the problems raised in this study is Effectiveness of linguistic environment on learning Arabic, This research uses descriptive qualitative through communicative approach method, from the two boarding schools the researcher finds that differences: 1). Boarding Schools Baitul Arqam Jember and al-Kautsar Sidoarjo using artificial language environments., 2). The influence of the language environment on the ability of students to speak Arabic has a very big impact when viewed from before and after using the language environment, including: before using the language environment, students in the two Islamic boarding schools do not know the daily greeting words and unable to speak Arabic, but after they use the language environment they can to speak using Arabic., 3). Weaknesses of language environment in Baitul Arqam Jember are the lack of student awareness in the application of language environment, while the advantages of language environment in this boarding schools that is the existence of language environment around the residence of students., while the shortcomings of language environment in the boarding al-Kautsar Sidoarjo, namely The lack of justification of sentences, The advantage of language environment al-Kautsar Sidoarjo is the teachers employees give examples of speaking Arabic in front of students.